Pendampingan Literasi Pasar Modal Syariah pada Galeri Investasi Edukasi (GIE) untuk meningkatkan Pengetahuan Gen-Z - Hak, Nurul; Yustati, Herlina; Sari, Widya Wulan (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2023)
The intention to invest began to grow among young people. 70% of millennials already know how to invest. The method used is Participation Action Research (PAR) which actively involves all relevant parties (stakeholders) in reviewing ongoing actions in order to make changes and improvements in a better direction. The purpose of this assistance is to increase Islamic capital market literacy in Generation Z at SMAN 07 Bengkulu City. Before the mentoring was carried out, the literacy level of the Islamic capital market at the Educational Investment Gallery (GIE) of SMAN 07 Bengkulu City was only 20%. Then at the end of the assistance, the Islamic capital market literacy level at GIE SMAN 07 increased to 65%. This is the output of mentoring activities in the form of a Level 1 Capital Markets School, Stocklab Education, and Training for Filling in the RDIS System.